Health inequalities, fundamental causes and power: towards the practice of good theory. Issue 1 (22nd November 2020) - McCartney, Gerry; Dickie, Elinor; Escobar, Oliver; Collins, Chik
Abstract: Reducing health inequalities remains a challenge for policy makers across the world. Beginning from Lewin's famous dictum that "there is nothing as practical as a good theory", this paper begins from an appreciative discussion of 'fundamental cause theory', emphasizing the elegance of its theoretical encapsulation of the challenge, the relevance of its critical focus for action, and its potential to support the practical mobilisation of knowledge in generating change. Moreover, it is argued that recent developments in the theory, provide an opportunity for further theoretical development focused more clearly on the concept of power (Dickie et al. 2015). A critical focus on power as the essential element in maintaining, increasing or reducing social and economic inequalities – including health inequalities – can both enhance the coherence of the theory, and also enhance the capacity to challenge the roots of health inequalities at different levels and scales. This paper provides an initial contribution by proposing a framework to help to identify the most important sources, forms and positions of power, as well as the social spaces in which they operate. Subsequent work could usefully test, elaborate and adapt this framework, or indeed ultimately replace it with something better, to help focus actions to reduce inequalities.